IT-enabled comprehensive building environmental assessment. (2016) - Lai, T.M.; To, W.M.; Ku, K.I.; Chung, A.W.L.
Building environmental assessment is a holistic approach that evaluates the environmental performance of a building from its planning, design, construction to its operation, maintenance and demolition, with the usability and functionality of the whole building system taken into consideration. Hence, not only a healthy, comfort and functional indoor environment can be achieved but also environmental impacts arisen from a building throughout its life cycle can be minimised. However, a building's environmental assessment cannot be performed without understanding the ingress of external pollution into the building as it affects the design of building envelope. The paper presents some 3D modelling approaches that determine noise and air pollution levels at the building envelope. An e-commerce web application for building environmental assessment was developed based on the well-established technology acceptance model (TAM). Using mobile and cloud technology, this App guides building designers to perform a detailed building environmental assessment in an interactive manner.